Physicochemical characterization and in vitro assessment of the nutritive value of starch yield from corn dried at different temperatures. Issue 7 (19th April 2014) - Malumba, Paul; Odjo, Sylvanus; Boudry, Christelle; Danthine, Sabine; Bindelle, Jérôme; Beckers, Yves; Béra, François
Abstract To assess modifications induced in starch granules during high temperature drying of corn grain and their effect on the nutritive value of corn‐starch, physicochemical and structural characteristics of starch granules from corn grains dried at different temperatures have been determined. Additionally, their in vitro digestibility and fermentation patterns were investigated, using a two steps in vitro model of the pig digestive tract. High drying temperatures induced a partial gelatinization of starch granules and produced a very favorable substrate for porcine pancreatic amylase and led to an altered physical structure which affected the rate and extent of starch granules digestion by gastric and pancreatic enzymes. Starch micrographs showed that granules extracted from corn dried at 130°C were less angular, bigger, and had smoother surface than granules extracted from corn dried at lower temperature. High‐temperature drying increased the digestibility of wet‐milled starch granules, while the residues of starch from corn dried at lower temperature produced higher volume of gas during their in vitro fermentation, despite their more pronounced crystalline characteristic. The residues from pepsin–pancreatic digestion of overall samples analyzed showed highly degraded and pitted granules or fragmented external shells, starch from corn dried at 130°C being the most degraded. Aforementioned changes of nutritional attributes of starch granules are discussed according to the restructuration occurring within both their amorphous and crystalline phase, as well as to the changes of the granules size and purity.